PEMBELAJARAN PROBLEM BASIC LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMAN UNGGUL ACEH TIMUR - nurleili (Jurnal Mahasiswa Akuntansi Samudra, 2021)
ABSTRACT Before the action was taken in class X Mipa-3, there were only 5 students (26%) of the 19 students in the class for the 2019/2020 academic year. Starting from family factors, environment, school, and several other factors. One of these factors is the use of learning strategies or methods. Based on this, in class X Mia 3, a class action research was then applied with the Problem Basic Learning learning model so that completeness could be maximized more optimally. This research was conducted at East Aceh Superior Senior High School for 3 months in the odd semester of the 2019/2029 school year which aims to improve the learning outcomes of class X Mipa-3 students on the material Pancasila values ​​in the framework of state administration practices. The research subjects were all students of class VII-3 who collected 19 people. In collecting data, the researcher used instruments or data collection techniques in the form of 10-item multiple choice test items, observation sheets and closed interviews. After collecting data, the researcher conducted data processing and analysis by comparing the test results and observations from the initial conditions, the first and second cycles. The results showed an increase in student mastery in the first cycle to 63% (12 students) from the initial condition which was only 26% (5 students), and at the end of the second cycle, completeness increased again to 89% (17 students).